Ammonium (NH4+): Nitrate (NO3-) ratio and its relation to the changes in solution pH, growth, mineral nutrition and yield of tomatoes grown in nutrient film technique - Ismail, Mohd Razi; Othman, Abd Aziz (Universiti Putra Malaysia Press, 1995)
The effects of NH4+ NO3- ratio on growth, water uptake, solution pH, mineral nutrition and yield of tomatoes were investigated using the nutrient film technique. There were six NH4+ NO3- ratios: 0:100 with and without pH control; 12.5:87.5, 25:75, 37.5:62.5 and 50:50 without pH control. There was an increase in pH of the nutrient solution with 0:100 and 12.5:87.5 ratios, but the pH decreased with 50:50 ratio. Higher NH4+ NO3- ratio reduced leaf and root growth. The reduction in leafand root growth could be attributed to reduction o fplant water uptake. Fruit fresh weight was reduced and the percentage of blossom-end rot increased with higher ratio of NH4+ NO3- in the solution. Increased ratio of NH4+ NO3- increased N content and decreased Ca content in all the plant tissues. P, K and Mg content decreased in leaf tissue with increasing NH4+ NO3- ratio.